2011
DOI: 10.1080/00330124.2011.583584
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking “Diversity” Through Analyzing Residential Segregation Among Hispanics in Phoenix, Miami, and Chicago

Abstract: Hispanics are an internally diverse population, yet residential segregation within census-defined groups is often overlooked. Census data are used to examine evenness and exposure segregation among Hispanics in Chicago, Miami, and Phoenix along the lines of national origin, race, year of arrival, and income. Results suggest that segregation exists in Miami where there is more national origin diversity, between white and black Hispanics in Chicago, in all three cities for foreign-born Hispanic recent arrivals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…According to 2000 census data, Miami was ranked 9th of U.S. southern cities for Black versus White indices of dissimilarity for cities with the largest Black population (Frey & Myers, 2005). Based on 2000 census data, Miami was ranked as the most segregated U.S. city for Hispanics; and especially high segregation was observed between Cubans, Haitians, Colombians, and Nicaraguans (Lukinbeal, Price, & Buell, 2012). Since Hispanics comprise 41 percent of Miami MSA's 2010 census population (U.S. Census 2010), the importance of disaggregating this ethnic category into appropriate subgroups based on country of origin and conducting intra-categorical EJ analysis of Hispanics in Miami is evident.…”
Section: Study Areamentioning
confidence: 99%
“…According to 2000 census data, Miami was ranked 9th of U.S. southern cities for Black versus White indices of dissimilarity for cities with the largest Black population (Frey & Myers, 2005). Based on 2000 census data, Miami was ranked as the most segregated U.S. city for Hispanics; and especially high segregation was observed between Cubans, Haitians, Colombians, and Nicaraguans (Lukinbeal, Price, & Buell, 2012). Since Hispanics comprise 41 percent of Miami MSA's 2010 census population (U.S. Census 2010), the importance of disaggregating this ethnic category into appropriate subgroups based on country of origin and conducting intra-categorical EJ analysis of Hispanics in Miami is evident.…”
Section: Study Areamentioning
confidence: 99%
“…'[T]he contemporary United States is becoming more residentially segregated and more diverse concurrently' (Wright et al, 2014: 176), both with respect to racialized segregation and mixing amongst broad racial categories, as well as within categories. Lukinbeal et al (2012) found Cuban and CubanAmerican self-segregation to be a driver of urban ethnic concentrations in Miami amongst Latinos.…”
Section: Diversifying Diversitymentioning
confidence: 97%
“…There are a few scholars, though, who have used income/class as a more important predictor of segregation compared to race/ethnicity, and have concluded that income-based within-group inequalities can be far greater than between-group differences caused by racism when explaining contemporary residential segregation patterns (De Oliver and Dawson-Munoz 1996). Likewise, Lukinbeal, Price, and Buell (2012), in their analyses of various within-group Hispanic segregation in Chicago, Miami, and Phoenix suggested that withingroup segregation by income was as significant as between-group segregation across the three study sites. Some scholars have also called it the 'Tortilla-Mercedes Divide' (Allen 2002)-largely referring to the strong roles of income and class in segregating communities.…”
Section: Conceptual Framework and Immigrants' Decentralizationmentioning
confidence: 99%